Lightweight and Flexible Solid-State EDLC based on Optimized CMC-NH4NO3 Solid Bio-Polymer Electrolyte - K. H. Kamarudin; M. Hassan; M. I. N. Isa (Akademi Sains Malaysia, 2024)
Volume:1 (Special Issues)